2021
DOI: 10.1186/s12985-021-01599-9
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of SARS-CoV-2 RNA in the nasopharyngeal, blood, urine, and stool samples of patients with COVID-19: a hospital-based longitudinal study

Abstract: Background The persistence of severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) RNA in the body fluids of patients with the novel coronavirus disease 2019 (COVID-19) may increase the potential risk of viral transmission. There is still uncertainty on whether the recommended quarantine duration is sufficient to reduce the risk of transmission. This study aimed to investigate the persistence of SARS-CoV-2 RNA in the nasopharyngeal, blood, urine, and stool samples of patients with COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
1
15
1
Order By: Relevance
“…Persistent viral shedding is a known marker of initial disease severity and varies extensively based on viral infection type, corticosteroid/antiretroviral treatment, and host immunity [ 8 , 30 ]. However, SARS-CoV-2 viral load has not necessarily correlated with disease severity, though current literature remains conflicting [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent viral shedding is a known marker of initial disease severity and varies extensively based on viral infection type, corticosteroid/antiretroviral treatment, and host immunity [ 8 , 30 ]. However, SARS-CoV-2 viral load has not necessarily correlated with disease severity, though current literature remains conflicting [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation for persistent viral RNA shedding is one method to track recovery and long-term response to severe viral infections. Detection of persistent viral shedding is influenced by initial disease severity, viral load, and sample source [ 8 – 10 ]. The phenomenon of persistent viral shedding is well-studied and demonstrated in numerous other viruses with broad public health impact, including avian influenza A [ 11 ], Zika [ 12 ], and Ebola [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study found no significant association between the persistence of SARS-CoV-2 positivity till the 6 th week with underlying comorbid conditions or demographic variables in the patients. This finding could be supported by the study by Joukaret al who stated that no significant associations were found between clinical and demographic characteristics of patients and duration of SARS-CoV-2 RNA persistence [20]. On the contrary, Shu et al reported that prolonged SARS-CoV-2 RNA positivity was significantly associated and underlying comorbid conditions (p = 0.029) [5].…”
Section: Discussionmentioning
confidence: 71%
“…14 Through a longitudinal study, Joukar et al showed persistence of the virus for a mean duration of 13 days compared with lower duration in blood and urine samples. 15…”
Section: Coronavirus and The Gi Tractmentioning
confidence: 99%